HOME BASED CARE BY PROVIDING PREVENTION OF MOTHERTO- CHILD TRANSMISSION (PMTCT) HANDBOOK ON WOMEN’S PERCEPTION OF HIV/AIDS PREVENTION IN MOTHER TO CHILD IN PURWOKERTO - Walin Walin; Dina Indrati Dyah Sulistyowati; Mardiyono Mardiyono; Ratifah Ratifah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Previous research, surveillance, and epidemic data of HIV/AIDS in Indonesia show the number of women and infants infected HIV/AIDS increases. Pregnant women with HIV/AIDS may transmit to their child. This is known as mother to child transmission (MTCT). Women with HIV/AIDS face several problems, such as physical, psychological, cognitive, social, cultural, and spiritual problems. Previous literatures, home based on care is a family approach to care for women with HIV/AIDS and handbook of preventive MTCT helps women improve their perception of HIV/AIDS prevention in mother to child. Aims: The research aimed to evaluate women’s perception of HIV/AIDS prevention in mother to child in Banyumas District in intervention and control group. Methods: The research was a two group pre-post quasi-experimental design. The research was conducted in Margono Soekarjo hospital and “Mandiri” shelter of HIV/AIDS in Purwokerto. The samples were recruited by purposive sampling method. The number of samples were 30 subjects; 15 subjects in intervention group in the shelter and 15 subjects in control group in the hospital. Home Based Care with PMTCT handbook was applied for a month with twice visit. Data were collected with Questionnaires of Perception of HIV/AIDS prevention in mother to child at pre and post intervention. Data were analyzed by paired and independent t-test. Results: The findings show that the scores of perception of HIV/AIDS prevention in mother to child within intervention increased significantly (p<0,00). There were significant differences of perception scores of HIV/AIDS prevention in mother to child between intervention and control group (p<0,00). The Home Based Care with PMTCT handbook could improve women’s perception of HIV/AIDS prevention in mother to child. Conclusion: The Home Based Care with PMTCT handbook can be implemented in home care or public health center and women with HIV/AIDS can follow the handbook to prevent infection from mother to child.